Effect of Hydrophilic Polymers on the Complexation, Solubilizing Efficiencies and Dissolution Rate Enhancement of Etoricoxib by Cyclodextrin Complexation - Chowdary, K.P.R.; Seetha Devi, A. (Asian Journal of Chemistry, 2011)
The objective of the present investigation is to study the complexation of etoricoxib with two cyclodextrins, β-cyclodextrin and hydroxy propyl β-cyclodextrin for enhancing its solubility and dissolution rate. The effect of three hydrophilic polymers namely poly(vinyl pyrrolidone) (PVP), hydroxy propyl methyl cellulose (HPMC) and polyethylene glycol (PEG) on the complexation and solubilizing efficiencies of cyclodextrins and on the dissolution rate and efficiency of etoricoxib from cyclodextrin complexes was also investigated. The aqueous solubility of etoricoxib was linearly increased as a function of the concentration of β-cyclodextrin and hydroxy propyl β-cyclodextrin alone and in the presence of hydrophilic polymers, PVP, HPMC and PEG. The increase in solubility is due to the formation of a 1:1 M complex in solution in each case. The complexes formed between etoricoxib- cyclodextrin were quite stable. Addition of hydrophilic polymers has markedly enhanced the complexation efficiency of cyclodextrins. Poly(vinyl pyrrolidone) has given higher enhancement in the complexation efficiency of both β-cyclodextrin and hydroxy propyl β-cyclodextrin. The order of hydrophilic polymers in enhancing the complexation efficiency was PVP > HPMC > PEG with both β-cyclodextrin and hydroxy propyl β-cyclodextrin. Addition of hydrophilic polymers has markedly enhanced the solubilizing efficiency of both β-cyclodextrin and hydroxy propyl β-cyclodextrin. Hydroxy propyl β-cyclodextrin exhibited higher solubilizing efficiency when compared to β-cyclodextrin, both alone and in the presence of hydrophilic polymers. Poly(vinyl pyrrolidone) has given highest enhancement (11.67-16.75 fold) in the solubilizing efficiency of cyclodextrins. cyclodextrin complexes gave rapid and higher dissolution of etoricoxib when compared to the pure drug. Hydroxy propyl β-cyclodextrin gave higher enhancement in the dissolution rate and efficiency when compared to β-cyclodextrin. Complexes prepared by kneading method gave higher dissolution rate and dissolution efficiency values than those prepared by co-precipitation and physical mixing methods. The hydrophilic polymers alone gave a marginal increase in the dissolution rate of etoricoxib addition of hydrophilic polymers has further enhanced the dissolution rate and efficiency of etoricoxib from cyclodextrin complexes. A 26.28 and 46.64 fold increase in the dissolution rate of etoricoxib was observed respectively with etoricoxib- β-cyclodextrin-PVP and etoricoxib- hydroxy propyl β-cyclodextrin-PVP complexes. Hence a combination of cyclodextrins and hydrophilic polymers is recommended for enhancing the complexation and solubilizing efficiencies of cyclodextrins and also for enhancing the dissolution rate of etoricoxib from cyclodextrin complexes.